1988
DOI: 10.1007/bf00200020
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor cells in the effector phase of autologous cytotoxic reactions in cancer patients

Abstract: Cytotoxicity was induced in lymphocytes (CL) from 10 out of 15 patients by autologous mixed lymphocyte tumor cell culture and further cultivation with recombinant interleukin-2. In cells from 3 of the 10 patients, cytotoxicity was suppressed by more than 50% when autologous peripheral blood mononuclear cells (PBMC) from the patients with large tumors were added to the autologous killing system. The cells responsible for suppressing the cytotoxicity in the effector phase were adherent or nonadherent to plastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Inhibition of NK activity mediated by suppressor lymphocytes and monocyte macrophages has been observed in mice during tumor development (Parhar and Lala, 1985;Young et al, 1986). Since unseparated PBLs were used to study NK activity, the suppressor cells present among the PBLs of cancer patients might be responsible for the observed deficient NK activity (Eura et al, 1988). The presence of such suppressor cells in PBLs of elderly healthy men might also explain the deficient NK activity observed in this group compared with that in their younger counterpart (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Inhibition of NK activity mediated by suppressor lymphocytes and monocyte macrophages has been observed in mice during tumor development (Parhar and Lala, 1985;Young et al, 1986). Since unseparated PBLs were used to study NK activity, the suppressor cells present among the PBLs of cancer patients might be responsible for the observed deficient NK activity (Eura et al, 1988). The presence of such suppressor cells in PBLs of elderly healthy men might also explain the deficient NK activity observed in this group compared with that in their younger counterpart (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…LNL are the next most immunosuppressed population of effector cells. Regional LNL have reduced NK and lymphokine‐activated killer (LAK) cell activities, mitogenic responses, and cytokine production when compared with PBL 44,45,72–75 . LNL in closer proximity to the primary tumor bed show weak response to IL‐2 stimulation compared with distally located LNL.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that a high ASTC CTL frequency was found even among lymphocytes harvested from PIR2-high cell-number LDC wells ( Table 1) also indicates that the suggested suppression is not operative at the level of induction of ASTC cells but rather on their cytotoxic activity at the effector phase; suppression ofthe induction of ASTC would have resulted in a reduced frequency of ASTC CTL among cells harvested from PIR-2 -high cell-number LDC wells. The existence of suppressor cells regulating autologous cytotoxicity at the effector phase has been recently reported in cancer patients (22). In addition, Joly et al (16) recently reported the existence of CD8+ class I-nonrestricted suppressor cells that suppress, at the effector phase, the cytotoxicity against autologous anti-HIV-infected target cells, as well as the activity of antiautologous HLA CTL.…”
Section: Discussionmentioning
confidence: 95%
“…Freshly obtained splenocytes or lymphocytes harvested from 5-d MLC were plated in LDC as previously described (5,18) . Briefly, graded numbers (10-50,000) of responding cells were cultured for 8-9 d in round-bottomed 96-well plates (Nunc) in [16][17][18][19][20][21][22][23][24] replicates, in the presence of 106/well of irradiated (30 Gy) allogeneic splenocytes and human rIL-2 (250 U/ml, Cetus Corp., Emeryville, CA) in a final volume of 0.2 ml complete DME. In some experiments (secondary LDC), the responding cells were obtained from selected LDC wells .…”
Section: Methodsmentioning
confidence: 99%